Infectious Cervical Pneumorachis with a Fatal Outcome: A Case Report - Pazardzhikliev, Dimitar (Brazilian Journal of Case Reports, 2024)
Pneumorachis is the presence of gas in the spinal canal. It is usually a result of trauma or iatrogenic, where it is usually asympomatic and is managed conservatively. However, pneumorachis due to gangrenous inflammation in vicinity is extremely rare and may be considered a sign of poor outcome. Necrotizing soft tissue infections are fulminant and life-threatening entity. In contrast to the localized deep neck infections, they spread swiftly, invading adjacent areas. We present a rare case of retropharyngeal necrotizing infection with involvement of the spinal canal and pneumorachis that has not been published before.